2017
DOI: 10.1080/00365521.2017.1282008
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of pediatric-onset IBD-unclassified and prediction of Crohn’s disease reclassification: a 27-year study

Abstract: In our cohort, a substantial high proportion of pediatric onset IBDU patients were later re-diagnosed as CD. Only a family history of CD and hypoalbuminemia could predict reclassification among IBDU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
1
23
2
Order By: Relevance
“…A shift in IBD diagnosis during a patient's medical history is even more common among patients who are initially diagnosed as IBD-U [12]. Previous studies have reported a shift to either Crohn's disease or ulcerative colitis among 23-84% of these patients [11,[13][14][15][16][17][18]. We previously reported a shift in IBD diagnosis at some point among 18% of patients with IBD in the NPR [12].…”
Section: Discussionmentioning
confidence: 77%
“…A shift in IBD diagnosis during a patient's medical history is even more common among patients who are initially diagnosed as IBD-U [12]. Previous studies have reported a shift to either Crohn's disease or ulcerative colitis among 23-84% of these patients [11,[13][14][15][16][17][18]. We previously reported a shift in IBD diagnosis at some point among 18% of patients with IBD in the NPR [12].…”
Section: Discussionmentioning
confidence: 77%
“…In other studies, 23-84% of patients with an initial diagnosis of IBD-U were later classified as UC or CD [9,12,24,[31][32][33]55]. In pediatric patients, a systematic review found an increase in diagnosis of CD over time, and a decrease in IBD-U [7].…”
Section: Discussionmentioning
confidence: 94%
“…The frequency of IBD-U is usually reported to be higher among pediatric patients compared to that of the adult population: 13 versus 6% in a meta-analysis [6], and to be decreasing over disease course [7]. In well characterized IBD cohorts, the proportion of IBD-U has been reported to range from 1 to 20% in adults [8][9][10][11][12][13][14][15][16][17][18][19][20] and from 4 to 22% in pediatric patients [21][22][23][24][25][26][27][28][29][30][31][32][33]) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Differentiating CD from UC is crucial for appropriate medical and surgical management of patients [ 1 2 ]. Some children with inflammatory bowel disease (IBD) do not show the typical endoscopic and histological findings of UC or CD, and up to 30% pediatric patients with IBD are diagnosed with IBD-unclassified (IBDU) [ 3 4 5 6 7 8 9 10 11 12 ]. The revised Porto criteria, the standardized diagnostic criteria for pediatric IBD, recommend using a combination of clinical symptoms, endoscopic findings, and histological findings for diagnosing IBD [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the importance of evaluating the upper gastrointestinal and small bowel regions beyond colonoscopy at initial diagnosis. Moreover, changes in diagnosis during follow-up have been reported in several studies on pediatric patients with IBD due to the development of small intestinal or perianal lesions and detection of epithelioid cell granulomas on histological analysis [ 3 4 8 9 11 12 14 15 16 ]. However, limited studies have revealed the clinical characteristics of patients whose diagnosis changed from UC to CD and the predictors of this diagnostic change.…”
Section: Introductionmentioning
confidence: 99%